Effectiveness of a Social Cognitive Theory-based health education intervention on depression (SCODESS) among mothers of children with cancer in Klang Valley, Selangor, Malaysia-A quasi-experimental study. - Wan Syahirah Wan Ghazali; Halimatus Sakdiah Minhat; Sherina Mohd Sidik; Iqmer Nashriq Mohd Nazan (PLoS ONE)
Background Mothers caring for children with cancer often experience depression, affecting maternal and family well-being. Prior studies suggest that theory-based health education can significantly reduce this depression. Objectives This study aimed to develop, validate, implement, and evaluate the effects of a Social Cognitive Theory (SCT)-based health education intervention on depression (SCODESS), as well as cancer-related knowledge, self-efficacy, perceived stress, coping skills, and social support among mothers of children with cancer at University Hospitals in Klang Valley. Methods A quasi-experimental study was conducted with mothers from two University Hospitals in Klang Valley, Selangor. The intervention group is Hospital Pakar Kanak-Kanak Universiti Kebangsaan Malaysia (HPKK UKM) and the control group is the Universiti Malaya Medical Centre (UMMC). A total of 95 participants were included (50 intervention, 45 control). The intervention comprised online health education videos delivered over one week, and the control group received a poster. Data were collected at baseline (T1), immediately post-intervention (T2), and at two months post-intervention (T3). The effects of SCODESS intervention were analysed using Generalised Estimating Equation (GEE) analysis. Results The baseline response rate was 60.53% with a 2.17% loss to follow-up at T2 and 7.60% at T3. The GEE analysis showed no significant effects of SCODESS intervention on depression scores at T2 (p = 0.909) and T3 (p = 0.622) compared to the control group at baseline. However, statistically significant increases were observed in cancer-related knowledge scores at T2 (β = 0.66, 95%CI: 0.21, 9.20, p = 0.002) and T3 (β = 1.18, 95%CI: 0.65, 1.70, p<0.001), and in the problem-focused coping scores at T2 (β = 2.50, 95% CI 0.42, 4.58, p-value = 0.018), and T3 (β = 2.42, 95% CI 0.13, 4.72, p-value = 0.038) in the intervention group compared to the control group at baseline. No significant intervention effects were observed on other outcomes. Discussion This study validated the applicability of SCT-based intervention on depression scores among mothers of children with cancer. The SCODESS intervention did not significantly reduce depression scores but significantly increased cancer-related knowledge and problem-focused coping scores. As a potential preventive strategy for depression, the content of the SCODESS intervention should be revisited, emphasizing cancer-related knowledge and problem-focused coping as crucial components. It is recommended that tailored interventions focusing on these areas be offered to every mother of children with cancer, whether they are in the ward, clinic, or daycare.